2008
DOI: 10.1002/cjce.5450830201
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Biofiltration of High-Loads of Toluene in Air: Carbon and Water Balances, Temperature Changes and Nitrogen Effect

Abstract: Biodegradable atmospheric pollutants, released at low to moderate concentrations, can be removed by biofiltration. In this work, a laboratory‐scale compost‐based biofilter has been evaluated for the removal of high levels of toluene in air (∼ 4.0 g.m−3). By applying a variable nitrogen input in the irrigation solution, it was shown that the biodegradation extent can be controlled through the nutrient supply. The maximum elimination capacity achieved was 135 g.m−3.h−1, for a N‐concentration of 3.0 g of N.L−1. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The results of these studies have shown that macrokinetic models fit well to the experimental EC. However, to our knowledge, these models have not been tested either on the BF or the BTF displaying inhibition due to concentration VOC, such as for methanol and for toluene (Delhoménie et al, 2005;Shareefdeen et al, 1993).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of these studies have shown that macrokinetic models fit well to the experimental EC. However, to our knowledge, these models have not been tested either on the BF or the BTF displaying inhibition due to concentration VOC, such as for methanol and for toluene (Delhoménie et al, 2005;Shareefdeen et al, 1993).…”
Section: Introductionmentioning
confidence: 94%
“…The source of this heat is the VOC biodegradation reaction (Mysliwiec et al, 2001). In order to calculate this energy, it is necessary to determine some parameters, such as the heat of combustion of the biofilm (Battley, 2003;Sandler, 1991) or the production of carbon dioxide (CO 2 ) (Delhoménie et al, 2005;Morales et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high Henry's law constant, alternative approaches can be used to treat contaminated water, such as gas stripping or gas stripping combined with biological treatment. Biological treatment approaches for removal of VOCs have certain advantages over physical and chemical techniques including low‐cost, effectiveness, higher safety, and eco‐friendly . Biofiltration is a biological process that uses microorganisms to convert water‐soluble VOCs into harmless by‐products.…”
Section: Introductionmentioning
confidence: 99%
“…Biological treatment approaches for removal of VOCs have certain advantages over physical and chemical techniques including low-cost, effectiveness, higher safety, and eco-friendly. 11 Biofiltration is a biological process that uses microorganisms to convert water-soluble VOCs into harmless by-products. Recently, there have been increasing interests in applying biofiltration for the removal of polluted waste-gas.…”
mentioning
confidence: 99%
“…Biofiltration is now one of the most cost-effective and sustainable off-gas treatment technologies due to its minimal energy requirements and low environmental impact [1,2]. Based on its simple operation and high removal efficiencies for both hydrophilic and hydrophobic volatile pollutants, biofiltration is the most popular biotechnologies for the treatment of odours and industrial volatile organic compounds (VOCs) [3,4].…”
Section: Introductionmentioning
confidence: 99%